Dimanganese(II) hydroxide vanadate, Mn(2)(OH)[VO(4)] - Sun, Kewen (International Union of Crystallography, 2014)
Dimanganese(II) hydroxide vanadate was obtained from hydrothermal reactions. The crystal structure of the title compound is isotypic with that of Zn(2)(OH)[VO(4)]. Three crystallographically independent Mn(2+) ions are present, one (site symmetry .m.) with a distorted trigonal-bipyramidal and two (site symmetries .m. and 1) with distorted octahedral coordination spheres. These polyhedra are linked through common edges, forming a corrugated layer-type of structure extending parallel to (100). A three-dimensional framework results via additional Mn—O—V—O—Mn connectivities involving the two different tetrahedral [VO(4)] units (each with point-group symmetry .m.). O—H⋯O hydrogen bonds (one bifurcated) between the OH functions (both with point-group symmetry .m.) and the [VO(4)] units complete this arrangement.